Dominican Republic : Sectoral Financial Positions and Macroeconomic Vulnerabilities - Cerovic, Svetlana (IMF Working Papers; Working Paper, 2016)
This paper examines the financial position of the key sectors of the Dominican Republic. It contributes to macroeconomic surveillance by identifying financial interlinkages and vulnerabilities through the balance sheet approach. The balance sheet of the economy has been weakening, particularly in foreign currency, due to persistent fiscal deficits. Risks arising from weaker foreign currency position, however, seem to be mitigated by long-term maturities on government debt and increasing accumulation of foreign currency assets. Given the strong links of the rest of the economy with the public sector, network analysis suggests that while the financial position of the other sectors of the economy is stronger, they could be adversely affected in an external stress scenario. Exposures to public sector are particularly pronounced in the domestic financial system (directly) and households (indirectly, through pension funds).